ANALISIS KEPADATAN PENDUDUK KECAMATAN SIMPANG ALAHAN MATI KABUPATEN PASAMAN - Maulida - Khairani; Sri Mariya (JURNAL BUANA, 2022)
This study aims to determine the population density of Simpang Alahan Mati District and the factors that affect population density. The type of this research is quantitative research with descriptive method, the subjects in this study are the people in Simpang Alahan Mati District, Pasaman Regency. The results showed that the birth rate was higher than the death rate and the immigration rate was higher than the emigration rate. This is what causes the high population density in Simpang Alahan Mati District, Pasaman Regency.